Self-compacting refractory concrete and preparation method thereof

By adding steel fibers, modified ethylene-vinyl acetate copolymer and maleic anhydride to the self-finished concrete, the problem of poor performance of existing self-finished concrete in high temperature environments is solved, and higher density, fire resistance and permeability are achieved.

CN116444220BActive Publication Date: 2025-02-28DEQING KAIRUI HIGH TEMPERATURE MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310394532.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-13
Publication Date
2025-02-28
Estimated Expiration
2043-04-13

AI Technical Summary

Technical Problem

The existing self-finished concrete has poor performance in high temperature environments, with high hydration heat and moisture evaporation leading to cracks, reducing density and compressive strength.

Method used

Adopt the self-contained refractory concrete formula containing steel fibers, modified ethylene-vinyl acetate copolymers and maleic anhydride to increase the adhesion and thermal insulation properties through microalgae oil.

Benefits of technology

It improves the density and fire resistance of concrete, enhances compressive strength and permeability, reduces porosity, and improves the overall toughness and bonding force of the structure.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a self-compacting refractory concrete and a preparation method thereof, comprising the following raw materials in parts by weight: 600-700 parts of coarse aggregate; 900-1000 parts of fine aggregate; 40-60 parts of fly ash; 300-600 parts of cement; 150-250 parts of water; 4-8 parts of water reducer; 10-20 parts of modified ethylene-vinyl acetate copolymer; 5-15 parts of steel fiber; 2-8 parts of maleic anhydride; the modified ethylene-vinyl acetate copolymer comprises ethylene-vinyl acetate copolymer and microalgae oil. The present application has the function of improving the fire resistance of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete, in particular to a self-compacting refractory concrete and a preparation method thereof. Background Art

[0002] During the concrete construction process, cast-in-place concrete is usually pumped and compacted using handheld vibrators. However, when faced with large-volume and large-span components, it is impossible to ensure uniform feeding and compaction. Therefore, self-compacting concrete is usually used to meet the needs. In recent years, with the increase in fire and electricity consumption, fire accidents have also occurred from time to time, and the performance of concrete in high temperature environments will drop sharply.

[0003] Existing self-compacting concrete has poor performance in high temperature environments. The hydration heat of concrete is high. The moisture in the high temperature environment will gradually evaporate, and many cracks will form inside the concrete. These cracks will reduce the density of the concrete, thereby reducing the mechanical properties of the concrete such as compressive strength, and destroying the structure of the concrete. Summary of the invention

[0004] In order to improve the fire resistance of concrete, the present application provides a self-compacting refractory concrete and a preparation method thereof.

[0005] In a first aspect, the present application provides a self-compacting refractory concrete using the following technical solution:

[0006] A self-compacting refractory concrete comprises the following raw materials in parts by weight: 600-700 parts of coarse aggregate; 900-1000 parts of fine aggregate; 40-60 parts of fly ash; 300-600 parts of cement; 150-250 parts of water; 4-8 parts of water reducing agent; 10-20 parts of modified ethylene-vinyl acetate copolymer; 5-15 parts of steel fiber; and 2-8 parts of maleic anhydride. The modified ethylene-vinyl acetate copolymer comprises ethylene-vinyl acetate copolymer and microalgae oil.

[0007] By adopting the above technical scheme, the present application incorporates steel fibers into the components for preparing self-compacting concrete, and the ethylene-vinyl acetate copolymer has good thermal insulation performance. The ethylene-vinyl acetate copolymer is modified by microalgae oil to increase the adhesion of the ethylene-vinyl acetate copolymer, so that the modified ethylene-vinyl acetate copolymer has good adhesion to coarse aggregate and fine aggregate in concrete, thereby improving the compactness of the concrete; at the same time, the modified ethylene-vinyl acetate copolymer forms a film on the surface of the concrete mixture, so that the concrete has good thermal insulation performance and improves the fire resistance of the concrete; the modified ethylene-vinyl acetate copolymer, steel fibers and maleic anhydride are combined together, and the maleic anhydride allows the steel fibers to be evenly dispersed in the cement mortar, effectively improving the fluidity and adhesion of the concrete mixture, thereby improving the fire resistance of the concrete.

[0008] Preferably, the preparation method of the modified ethylene-vinyl acetate copolymer is: heating 20-30 parts by weight of ethylene-vinyl acetate copolymer; heating 10-20 parts by weight of microalgae oil, pouring the heated microalgae oil into the ethylene-vinyl acetate copolymer, stirring at a low speed and then at a high speed to obtain the modified ethylene-vinyl acetate copolymer; the microalgae oil includes yellow silk algae microalgae liquid, green golden algae microalgae liquid, Spirulina microalgae liquid, copper sulfate and n-hexane.

[0009] By adopting the above technical scheme: microalgae oil is obtained by extracting a variety of microalgae liquids, and then ethylene-vinyl acetate copolymer is modified by microalgae oil. The modified ethylene-vinyl acetate copolymer has vinyl double bonds, carboxyl groups and other groups. The more unsaturated groups can promote the modified ethylene-vinyl acetate copolymer to form a network molecular structure in the concrete mixture, increase the contact area between the modified ethylene-vinyl acetate copolymer and the concrete mixture, improve the overall toughness of the concrete mixture, improve the bonding strength with the concrete mixture, and then improve the density of the concrete.

[0010] Preferably, the preparation method of the microalgae oil is: 2-8 parts by weight of yellow silk algae microalgae liquid, 2-8 parts by weight of green golden algae microalgae liquid and 2-8 parts by weight of Spirulina microalgae liquid are mixed and inactivated by ultraviolet irradiation to obtain a microalgae liquid; 0.2-0.5 parts by weight of copper sulfate is added to the microalgae liquid and left at room temperature for 20-25 hours to obtain a microalgae suspension; the microalgae suspension is centrifuged and filtered; the filter residue is dried, then added with n-hexane, stirred and allowed to stand, heated and distilled, and extracted to obtain the microalgae oil.

[0011] By adopting the above technical scheme, the microalgae liquid formed by the yellow filament algae microalgae liquid, the green golden algae microalgae liquid, and the spirulina microalgae liquid supports the microalgae oil through multiple processes. The microalgae oil is extracted through multiple biological microalgae. The microalgae is subjected to long-term light growth in a natural environment. The unique growth environment improves the performance of the microalgae oil, so that the prepared microalgae oil can effectively improve the thermal insulation performance of the modified ethylene-vinyl acetate copolymer after modifying the ethylene-vinyl acetate copolymer.

[0012] Preferably, the weight ratio of the yellow silk algae liquid, the green golden algae liquid and the spirulina microalgae liquid is (0.72-0.96):1:(1.12-1.28).

[0013] By adopting the above technical scheme, when the yellow filament algae microalgae liquid, the green golden algae microalgae liquid and the spirulina microalgae liquid are in a specific weight ratio, multiple microalgae liquids are mixed together, and the prepared microalgae oil enables the modified ethylene-vinyl acetate copolymer to maintain the original physical and chemical properties, while expanding the performance of the modified ethylene-vinyl acetate copolymer, improving the mechanical properties of the modified ethylene-vinyl acetate copolymer, and then the modified ethylene-vinyl acetate copolymer reduces the porosity of the concrete and improves the activity of the modified ethylene-vinyl acetate copolymer, thereby preparing concrete with higher density and anti-permeability performance.

[0014] Preferably, the weight ratio of the ethylene-vinyl acetate copolymer to the microalgae oil is (1.6-1.8):1.

[0015] By adopting the above technical scheme, when ethylene-vinyl acetate copolymer and microalgae oil are in a specific weight ratio, the microalgae oil adheres to the surface of the ethylene-vinyl acetate copolymer, and the modified ethylene-vinyl acetate copolymer can fill the gap between cement and concrete in concrete, reducing the porosity of the concrete and improving the density and heat resistance of the concrete.

[0016] Preferably, the steel fiber is a modified steel fiber, and the preparation method of the modified steel fiber is: soaking 10-20 parts by weight of steel fiber in 20-40 parts by weight of acetone solution for 12-24 hours and then drying, mixing 2-6 parts by weight of xylene, 3-9 parts by weight of benzophenone and 5-10 parts by weight of xanthan gum and then mixing with the dried steel fiber, and letting it stand for 20-40 minutes; irradiating with ultraviolet light for 15-25 minutes and then letting it stand, filtering and drying to obtain the modified steel fiber.

[0017] By adopting the above technical scheme, the present application modifies the steel fiber, and the bonding strength between the steel fiber and the concrete is one of the controlling factors of the reinforcement effect of the steel fiber on the concrete. The steel fiber is modified by xylene, benzophenone and xanthan gum, so that the steel fiber has better fire resistance in concrete.

[0018] Preferably, the weight ratio of the steel fiber, xylene, benzophenone and xanthan gum is (3-3.75):1:(1.05-1.35):(2-2.4).

[0019] By adopting the above technical scheme, when steel fiber, xylene, benzophenone and xanthan gum are in a specific weight ratio, xylene, benzophenone and xanthan gum modify the surface of steel fiber so that the surface of steel fiber has higher surface energy and chemical activity. When the modified steel fiber fills the gap in cement mortar, the concrete structure becomes denser, the mechanical properties of concrete are enhanced, and the anti-permeability performance of concrete is improved.

[0020] Preferably, the weight ratio of the modified ethylene-vinyl acetate copolymer, the modified steel fiber and maleic anhydride is 1:(0.36-0.48):(0.4-0.5).

[0021] By adopting the above technical scheme, when the modified ethylene-vinyl acetate copolymer, modified steel fiber and maleic anhydride are in a specific weight ratio, the three cooperate with each other, which can improve the fire resistance of concrete while also improving the anti-penetration performance of concrete, making the concrete structure denser.

[0022] Preferably, the water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent.

[0023] By adopting the above technical solution, the water reducing agent uses a polycarboxylic acid-based water reducing agent with good dispersibility, thereby improving the compactness and heat resistance of the concrete.

[0024] In a second aspect, the present application provides a method for preparing a self-compacting refractory concrete using the following technical solution:

[0025] A method for preparing a self-compacting refractory concrete comprises the following steps:

[0026] Mix the coarse aggregate, fine aggregate and fly ash and then add the steel fiber and continue mixing;

[0027] Cement, modified ethylene-vinyl acetate copolymer and maleic anhydride are added and stirred continuously, and then a water reducing agent and water are added and stirred sufficiently to obtain the self-compacting refractory concrete.

[0028] By adopting the above technical solution, the fire resistance of the concrete obtained by mixing various raw materials in multiple times is better.

[0029] In summary, this application has the following technical solutions:

[0030] 1. The present application incorporates steel fibers into the components for preparing self-compacting concrete. Ethylene-vinyl acetate copolymer has good thermal insulation performance. The ethylene-vinyl acetate copolymer is modified by microalgae oil to increase the adhesion of the ethylene-vinyl acetate copolymer, so that the modified ethylene-vinyl acetate copolymer has good adhesion to coarse aggregate and fine aggregate in concrete, thereby improving the compactness of the concrete; at the same time, the modified ethylene-vinyl acetate copolymer forms a film on the surface of the concrete mixture, so that the concrete has good thermal insulation performance and improves the fire resistance of the concrete; the modified ethylene-vinyl acetate copolymer, steel fibers and maleic anhydride are combined together, and the maleic anhydride allows the steel fibers to be evenly dispersed in the cement mortar, effectively improving the fluidity and adhesion of the concrete mixture, thereby improving the fire resistance of the concrete.

[0031] 2. The microalgae oil obtained by extracting a variety of microalgae liquids is then used to modify the ethylene-vinyl acetate copolymer. The modified ethylene-vinyl acetate copolymer has vinyl double bonds, carboxyl groups and other groups. The more unsaturated groups can promote the modified ethylene-vinyl acetate copolymer to form a network molecular structure in the concrete mixture, increase the contact area between the modified ethylene-vinyl acetate copolymer and the concrete mixture, improve the overall toughness of the concrete mixture, improve the bonding strength with the concrete mixture, and then improve the density of the concrete.

[0032] 3. When steel fiber, xylene, benzophenone and xanthan gum are in a specific weight ratio, xylene, benzophenone and xanthan gum modify the surface of steel fiber, so that the surface of steel fiber has higher surface energy and chemical activity. When the modified steel fiber fills the gap in cement mortar, the concrete structure is more compact, the mechanical properties of concrete are enhanced, and the anti-permeability of concrete is improved. DETAILED DESCRIPTION

[0033] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0034] Preparation Example

[0035] Preparation Example 1

[0036] A method for preparing microalgae oil:

[0037] 2kg of yellow silk algae microalgae liquid, 2kg of green golden algae microalgae liquid and 2kg of spirulina microalgae liquid are mixed and cultivated for 7 days to obtain microalgae liquid; after irradiating the microalgae liquid with ultraviolet light for 4 hours, 0.2kg of copper sulfate is added and left at room temperature for 20 hours to obtain a microalgae suspension; the microalgae suspension is added into a centrifugal filter for filtration to obtain a microalgae residue; the microalgae residue is placed in an oven at a temperature of 110°C for 3 hours to dry until the water is completely volatilized to obtain a dry microalgae residue; 5kg of n-hexane is added to the dry forged residue, fully stirred for 60 minutes and then allowed to stand for 24 hours, and the filtered filtrate is heated for distillation and extraction at a temperature of 75°C to fully volatilize the n-hexane to obtain microalgae oil.

[0038] Preparation Example 2

[0039] A method for preparing microalgae oil:

[0040] 8 kg of yellow silk algae microalgae liquid, 8 kg of green golden algae microalgae liquid and 8 kg of spirulina microalgae liquid are mixed and cultivated for 7 days to obtain a microalgae liquid; after irradiating the microalgae liquid with an ultraviolet lamp for 4 hours, 0.5 kg of copper sulfate is added and left at room temperature for 25 hours to obtain a microalgae suspension; the microalgae suspension is added into a centrifugal filter for filtration to obtain a microalgae residue; the microalgae residue is placed in an oven at a temperature of 110°C for 3 hours to dry until the water is completely volatilized to obtain a dry microalgae residue; 5 kg of n-hexane is added to the dry forged residue, the mixture is fully stirred for 60 minutes and then left to stand for 24 hours, and the filtered filtrate is heated for distillation and extraction at a temperature of 75°C to fully volatilize the n-hexane to obtain microalgae oil.

[0041] Preparation Example 3

[0042] A method for preparing microalgae oil, which is different from Preparation Example 1 in that the input amount of the yellow silk algae microalgae liquid is 3.6 kg, the input amount of the green golden algae microalgae liquid is 5 kg, and the input amount of the spirulina microalgae liquid is 5.6 kg.

[0043] Preparation Example 4

[0044] A method for preparing microalgae oil, which is different from Preparation Example 1 in that the input amount of the yellow silk algae microalgae liquid is 4.8 kg, the input amount of the green golden algae microalgae liquid is 5 kg, and the input amount of the spirulina microalgae liquid is 6.4 kg.

[0045] Example

[0046] Example 1

[0047] A method for preparing self-compacting refractory concrete:

[0048] Put 60kg of coarse aggregate, 90kg of fine aggregate and 4kg of fly ash into a mixer and mix for 90s. After the mixture is evenly mixed, add 0.5kg of steel fiber and continue to mix for 180s.

[0049] 30 kg of cement, 1 kg of modified ethylene-vinyl acetate copolymer and 0.2 kg of maleic anhydride were added and stirred at 50 ° C for 90 seconds, and then 0.4 kg of water reducer and 15 kg of water were added and stirred for 30 seconds to obtain self-compacting refractory concrete.

[0050] The preparation method of the modified ethylene-vinyl acetate copolymer is as follows:

[0051] 20 kg of ethylene-vinyl acetate copolymer was heated to 120° C.; 10 kg of the microalgae oil prepared in Preparation Example 1 was heated to 120° C., the heated microalgae oil was poured into the ethylene-vinyl acetate copolymer, and stirred at a low speed of 800 r / min and a temperature of 150° C. for 15 min, and then stirred at a high speed of 3600 r / min for 20 min to obtain a modified ethylene-vinyl acetate copolymer.

[0052] The melt index of ethylene-vinyl acetate copolymer is 150, and Exxon model UL15028 is selected;

[0053] The steel fiber used is Zhitai 8050 model.

[0054] Example 2

[0055] A method for preparing self-compacting refractory concrete:

[0056] 70kg of coarse aggregate, 100kg of fine aggregate and 6kg of fly ash were put into a mixer and mixed for 90s. After the mixture was evenly mixed, 1.5kg of steel fiber was added and the mixture was mixed for another 180s.

[0057] 60 kg of cement, 2 kg of modified ethylene-vinyl acetate copolymer and 0.8 kg of maleic anhydride were added and stirred at 50 ° C for 90 seconds, and then 0.8 kg of water reducer and 25 kg of water were added and stirred for 30 seconds to obtain self-compacting refractory concrete.

[0058] The preparation method of the modified ethylene-vinyl acetate copolymer is as follows:

[0059] 20 kg of ethylene-vinyl acetate copolymer was heated to 120° C.; 10 kg of the microalgae oil prepared in Preparation Example 1 was heated to 120° C., the heated microalgae oil was poured into the ethylene-vinyl acetate copolymer, and stirred at a low speed of 800 r / min and a temperature of 150° C. for 15 min, and then stirred at a high speed of 3600 r / min for 20 min to obtain a modified ethylene-vinyl acetate copolymer.

[0060] Example 3

[0061] A self-compacting refractory concrete and preparation method thereof:

[0062] Put 65kg of coarse aggregate, 95kg of fine aggregate and 5kg of fly ash into a mixer and mix for 90s. After the mixture is evenly mixed, add 1kg of steel fiber and continue to mix for 180s.

[0063] 45 kg of cement, 1.5 kg of modified ethylene-vinyl acetate copolymer and 0.5 kg of maleic anhydride were added and stirred at 50 ° C for 90 seconds, and then 0.6 kg of water reducer and 20 kg of water were added and stirred for 30 seconds to obtain self-compacting refractory concrete.

[0064] The preparation method of the modified ethylene-vinyl acetate copolymer is as follows:

[0065] 20 kg of ethylene-vinyl acetate copolymer was heated to 120° C.; 10 kg of the microalgae oil prepared in Preparation Example 1 was heated to 120° C., the heated microalgae oil was poured into the ethylene-vinyl acetate copolymer, and stirred at a low speed of 800 r / min and a temperature of 150° C. for 15 min, and then stirred at a high speed of 3600 r / min for 20 min to obtain a modified ethylene-vinyl acetate copolymer.

[0066] Example 4

[0067] A method for preparing a self-compacting refractory concrete is different from Example 3 in that, in the method for preparing the modified ethylene-vinyl acetate copolymer, the input amount of the ethylene-vinyl acetate copolymer is 30 kg; and the input amount of the microalgae oil is 20 kg.

[0068] Example 5

[0069] A method for preparing a self-compacting refractory concrete is different from Example 3 in that, in the method for preparing the modified ethylene-vinyl acetate copolymer, the input amount of the ethylene-vinyl acetate copolymer is 24 kg; the input amount of the microalgae oil is 15 kg.

[0070] Example 6

[0071] A method for preparing a self-compacting refractory concrete is different from Example 3 in that, in the method for preparing the modified ethylene-vinyl acetate copolymer, the input amount of the ethylene-vinyl acetate copolymer is 27 kg; the input amount of the microalgae oil is 15 kg.

[0072] Example 7

[0073] A method for preparing a self-compacting refractory concrete is different from Example 6 in that, in the method for preparing modified ethylene-vinyl acetate copolymer, an equal amount of the microalgae oil prepared in Preparation Example 1 is replaced by the microalgae oil prepared in Preparation Example 2.

[0074] Example 8

[0075] A method for preparing a self-compacting refractory concrete is different from Example 6 in that, in the method for preparing the modified ethylene-vinyl acetate copolymer, an equal amount of the microalgae oil prepared in Preparation Example 1 is replaced by the microalgae oil prepared in Preparation Example 3.

[0076] Example 9

[0077] A method for preparing a self-compacting refractory concrete is different from Example 6 in that, in the method for preparing the modified ethylene-vinyl acetate copolymer, an equal amount of the microalgae oil prepared in Preparation Example 1 is replaced by the microalgae oil prepared in Preparation Example 4.

[0078] Example 10

[0079] A method for preparing a self-compacting refractory concrete, which is different from Example 9 in that the steel fiber is a modified steel fiber, and the preparation method of the modified steel fiber is as follows: 10 kg of steel fiber is soaked in a 20 kg acetone solution for 24 hours and then dried at a temperature of 80 ° C, 2 kg of xylene, 3 kg of benzophenone and 5 kg of xanthan gum are stirred evenly at a temperature of 60 ° C and then mixed with the dried steel fiber, and allowed to stand for 30 minutes; ultraviolet irradiation is performed for 20 minutes, then allowed to stand for 30 minutes, filtered and then dried at a temperature of 80 ° C to obtain the modified steel fiber.

[0080] Embodiment 11

[0081] A method for preparing a self-compacting refractory concrete, which is different from Example 9 in that the steel fiber is a modified steel fiber, and the preparation method of the modified steel fiber is as follows: 20 kg of steel fiber is soaked in a 40 kg acetone solution for 24 hours and then dried at a temperature of 80 ° C, 6 kg of xylene, 9 kg of benzophenone and 10 kg of xanthan gum are stirred evenly at a temperature of 60 ° C and then mixed with the dried steel fiber, and allowed to stand for 30 minutes; ultraviolet irradiation is performed for 20 minutes, then allowed to stand for 30 minutes, filtered and then dried at a temperature of 80 ° C to obtain the modified steel fiber.

[0082] Example 12

[0083] A method for preparing self-compacting refractory concrete, which is different from Example 10 in that the input amount of steel fiber is 12 kg, the input amount of xylene is 4 kg, the input amount of benzophenone is 4.2 kg, and the input amount of xanthan gum is 8 kg.

[0084] Example 13

[0085] A method for preparing self-compacting refractory concrete, which is different from Example 10 in that the input amount of steel fiber is 15 kg, the input amount of xylene is 4 kg, the input amount of benzophenone is 5.4 kg, and the input amount of xanthan gum is 9.6 kg.

[0086] Embodiment 14

[0087] A method for preparing self-compacting refractory concrete, which is different from Example 13 in that the input amount of modified ethylene-vinyl acetate copolymer is 15 kg, the input amount of modified steel fiber is 7.2 kg, and the input amount of maleic anhydride is 6 kg.

[0088] Embodiment 15

[0089] A method for preparing self-compacting refractory concrete, which is different from Example 13 in that the input amount of modified ethylene-vinyl acetate copolymer is 15 kg, the input amount of modified steel fiber is 8.4 kg, and the input amount of maleic anhydride is 7.5 kg.

[0090] Comparative Example

[0091] Comparative Example 1

[0092] A method for preparing a self-compacting refractory concrete, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer is replaced by an ethylene-vinyl acetate copolymer in equal amounts.

[0093] Comparative Example 2

[0094] A method for preparing self-compacting refractory concrete, which is different from Example 1 in that steel fibers are replaced by glass fibers in equal amounts.

[0095] Comparative Example 3

[0096] A method for preparing a self-compacting refractory concrete, which is different from Example 1 in that maleic anhydride is not added.

[0097] Performance testing:

[0098] Fire strength test: According to GB / T50081-2016 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", standard test blocks were made from Examples 1-15 and Comparative Examples 1-3 and cured for 28 days; the cured concrete test blocks were placed in a muffle furnace at 600°C for 60 minutes, taken out, and tested for the fire strength of the concrete after natural cooling.

[0099] Anti-penetration performance: The chloride ion penetration depth of standard test blocks made of the concrete prepared in Examples 1-15 and Comparative Examples 1-3 was tested according to the rapid chloride ion migration coefficient method in GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete".

[0100] Fire strength MPa Chloride ion penetration depth mm Example 1 50.4 3.6 Example 2 50.7 3.5 Example 3 50.8 3.4 Example 4 50.6 3.5 Example 5 52.8 3.5 Example 6 52.5 3.4 Example 7 52.6 3.1 Example 8 53.2 3.2 Example 9 53.4 3.1 Example 10 56.1 3.0 Embodiment 11 56.4 3.2 Example 12 56.6 3.1 Example 13 56.5 3.0 Embodiment 14 58.3 2.6 Embodiment 15 58.7 2.5 Comparative Example 1 34.6 5.3 Comparative Example 2 41.3 4.8 Comparative Example 3 43.2 4.5

[0101] According to the data comparison of Examples 1-3 and Comparative Examples 1-3, it can be obtained that the present application incorporates steel fibers into the components for preparing self-compacting concrete, and ethylene-vinyl acetate copolymer has good thermal insulation performance. The ethylene-vinyl acetate copolymer is modified by microalgae oil to increase the adhesion of the ethylene-vinyl acetate copolymer, so that the modified ethylene-vinyl acetate copolymer has a good adhesion effect on coarse aggregate and fine aggregate in concrete, thereby improving the compactness of the concrete; at the same time, the modified ethylene-vinyl acetate copolymer forms a film on the surface of the concrete mixture, so that the concrete has good thermal insulation performance and improves the fire resistance of the concrete; the modified ethylene-vinyl acetate copolymer, steel fibers and maleic anhydride are combined together, and the maleic anhydride allows the steel fibers to be evenly dispersed in the cement mortar, effectively improving the fluidity and adhesion of the concrete mixture, thereby improving the fire resistance of the concrete.

[0102] According to the data comparison of Examples 3-6, when ethylene-vinyl acetate copolymer and microalgae oil are in a specific weight ratio, the microalgae oil adheres to the surface of the ethylene-vinyl acetate copolymer, and the modified ethylene-vinyl acetate copolymer can fill the gap between cement and concrete in concrete, reducing the porosity of the concrete and improving the density and heat resistance of the concrete.

[0103] According to the data comparison of Examples 6-9, when the yellow filament algae liquid, the green golden algae liquid and the spirulina microalgae liquid are in a specific weight ratio, the various microalgae liquids are mixed together, and the prepared microalgae oil enables the modified ethylene-vinyl acetate copolymer to maintain the original physical and chemical properties, while expanding the performance of the modified ethylene-vinyl acetate copolymer, improving the mechanical properties of the modified ethylene-vinyl acetate copolymer, and thereby enabling the modified ethylene-vinyl acetate copolymer to reduce the porosity of the concrete and improve the activity of the modified ethylene-vinyl acetate copolymer, thereby obtaining concrete with higher density and anti-permeability performance.

[0104] According to the data comparison of Examples 9-13, it can be obtained that the steel fiber is modified by xylene, benzophenone and xanthan gum, so that the steel fiber has better fire resistance in concrete; when the steel fiber, xylene, benzophenone and xanthan gum are in a specific weight ratio, xylene, benzophenone and xanthan gum modify the surface of the steel fiber, so that the surface of the steel fiber has higher surface energy and chemical activity, and when the modified steel fiber fills the gap in the cement mortar, the concrete structure is denser, the mechanical properties of the concrete are enhanced, and the anti-permeability performance of the concrete is improved.

[0105] According to the data comparison of Examples 13-15, it can be obtained that when the modified ethylene-vinyl acetate copolymer, the modified steel fiber and the maleic anhydride are in a specific weight ratio, the three cooperate with each other to improve the fire resistance of the concrete while also improving the anti-penetration performance of the concrete, making the concrete structure denser.

[0106] The specific embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A self-compacting refractory concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 600-700 parts of coarse aggregate; 900-1000 parts of fine aggregate; 40-60 parts of fly ash; 300-600 parts of cement; 150-250 parts of water; 4-8 parts of water reducing agent; 10-20 parts of modified ethylene-vinyl acetate copolymer; 5-15 parts of steel fiber; and 2-8 parts of maleic anhydride. The modified ethylene-vinyl acetate copolymer comprises ethylene-vinyl acetate copolymer and microalgae oil.

2. A self-compacting refractory concrete according to claim 1, characterized in that: The preparation method of the modified ethylene-vinyl acetate copolymer comprises: heating 20-30 parts by weight of ethylene-vinyl acetate copolymer; heating 10-20 parts by weight of microalgae oil, pouring the heated microalgae oil into the ethylene-vinyl acetate copolymer, stirring at a low speed and then at a high speed to obtain the modified ethylene-vinyl acetate copolymer; the microalgae oil comprises yellow silk algae microalgae liquid, green golden algae microalgae liquid, spirulina microalgae liquid, copper sulfate and n-hexane.

3. A self-compacting refractory concrete according to claim 2, characterized in that: The preparation method of the microalgae oil comprises the following steps: mixing 2-8 parts by weight of yellow silk algae microalgae liquid, 2-8 parts by weight of green golden algae microalgae liquid and 2-8 parts by weight of spirulina microalgae liquid, and then inactivating the mixture by ultraviolet irradiation to obtain a microalgae liquid; adding 0.2-0.5 parts by weight of copper sulfate to the microalgae liquid, and placing the mixture at room temperature for 20-25 hours to obtain a microalgae suspension; centrifuging the microalgae suspension; drying the filter residue, adding n-hexane, stirring and standing the mixture, heating and distilling the mixture, and extracting the mixture to obtain the microalgae oil.

4. A self-compacting refractory concrete according to claim 3, characterized in that: The weight ratio of the yellow silk algae liquid, the green golden algae liquid and the spirulina liquid is (0.72-0.96):1:(1.12-1.28).

5. A self-compacting refractory concrete according to claim 2, characterized in that: The weight ratio of the ethylene-vinyl acetate copolymer to the microalgae oil is (1.6-1.8):

1.

6. A self-compacting refractory concrete according to claim 1, characterized in that: The steel fiber is a modified steel fiber. The preparation method of the modified steel fiber is as follows: 10-20 parts by weight of steel fiber are soaked in 20-40 parts by weight of acetone solution for 12-24 hours and then dried; 2-6 parts by weight of xylene, 3-9 parts by weight of benzophenone and 5-10 parts by weight of xanthan gum are mixed and stirred, and then mixed with the dried steel fiber, and allowed to stand for 20-40 minutes; ultraviolet irradiation is performed for 15-25 minutes, then allowed to stand, filtered and then dried to obtain the modified steel fiber.

7. A self-compacting refractory concrete according to claim 6, characterized in that: The weight ratio of the steel fiber, xylene, benzophenone and xanthan gum is (3-3.75):1:(1.05-1.35):(2-2.4).

8. A self-compacting refractory concrete according to claim 6, characterized in that: The weight ratio of the modified ethylene-vinyl acetate copolymer, the modified steel fiber and maleic anhydride is 1: (0.36-0.48): (0.4-0.5).

9. The self-compacting refractory concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent.

10. A method for preparing a self-compacting refractory concrete, characterized in that: The method for preparing a self-compacting refractory concrete according to any one of claims 1 to 9 comprises the following steps: Mix the coarse aggregate, fine aggregate and fly ash and then add the steel fiber and continue mixing; Cement, modified ethylene-vinyl acetate copolymer and maleic anhydride are added and stirred continuously, and then a water reducing agent and water are added and stirred sufficiently to obtain the self-compacting refractory concrete.

Citation Information

Patent Citations

  • Permeable concrete powder reinforcing agent as well as preparation method and using method thereof

    CN109761529A

  • C60 concrete and preparation method thereof

    CN115636642A